Dynamic evolution of attribution analysis of runoff based on the complementary Budyko equation in the source area of Lancang river - Yang, Xu; Wang, Chao; Du, Jun; Qiu, Shike; Liu, Jiping (Frontiers in Earth Science, 2023)
Analyzing runoff variation characteristics and quantifying the impact of different factors on the runoff variation in the source area of Lancang River, are significant for scientific response to the ecological protection of the region and Lancang River. The Budyko method is adopted to quantitatively calculate the contribution rate of human factors and climate factors to runoff change in the source area of Lancang River. The results show that: (1) the annual runoff at Qamdo hydrological station decreased significantly during 1961-2018. (2) 1966 is the mutation year of runoff at Qamdo hydrological station from 1961 to 2018. (3) At the Qamdo hydrological station, the contribution rates of precipitation (P) to the runoff change are 16.92~72.8% before 1990 and -1.91~-53.61% after 1990, the contribution rates of potential evapotranspiration (ET0) to the runoff changes are 0.14~39.19%. The contribution rates of human factors (ω) to the runoff changes are between 26.9% and 114.42%. This study has important theoretical reference and practical significant for maintaining the integrity and sustainable development of the ecosystems of the Lancang River.